Assessing the Effectiveness of Phase Change Materials in Residential Buildings for Reducing Urban Heat Island Effects - Gunarani Gunaseelan Indrani; Rathinakumar Vedachalam; Selvakumar Radhakrishnan; Anirudh Raajan Varatharaajan; Ajay Bala Vikas Chelladurai; Aravind Chandramouli (Earth, 2025)
The Urban Heat Island’s (UHI) effect intensifies thermal discomfort for urban communities, increasing energy requirements. This study assesses the incorporation of Phase Change Materials (PCMs) into building envelopes to reduce Urban Heat Island (UHI) impacts in the Trichy urban area, characterised by a dry-summer tropical savanna environment. To evaluate energy efficiency and indoor temperature regulation, simulations were conducted using Design Builder and Climate 6.0 software. The results show that overall room electricity consumption decreased from 480 kWh to 380 kWh, demonstrating the energy-saving benefits of the modifications. Overall energy consumption was reduced to 271.9 kWh/m2/year from 312.23 kWh/m2/year in the base case, a 13% decrease, equating to 40.33 kWh/m2/year in energy savings. The payback period for PCM installation was predicted to be around 30.64 years. These results show that PCM-enhanced building envelopes reduce UHI effects and improve thermal comfort and energy efficiency, making them a feasible, sustainable urban development strategy.